Swedish quantitative criminology in the 1990s: A brief overview - Wikström, Per-Olof H. (Journal of quantitative criminology, 1996)
Quantitative criminology research published in Sweden in the 1990s is reviewed and put in the context of major Swedish traditions in quantitative criminological research. Sweden has a strong tradition in sophisticated longitudinal and ecological research which continues into the 1990s. Other traditionally prominent areas of Swedish quantitative research include studies of crime trends, violence, and youth criminality. Traditionally Swedish quantitative criminology has been dominated by studies using official statistics and criminal records as data. In the 1990s there has been a significant upswing in survey studies, motivated partly by an increased interest in questions of etiology and crime prevention. More fundamental research on the causes of crime, including new longitudinal studies, and more evaluations of crime prevention initiatives are needed.